The effect of ZnO loading for the enhancement of PSF/ZnO-GO mixed matrix membrane performance - Nurul ‘Adilah Rosnan,; Haan, Teow Yeit; Abdul Wahab Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was aimed to investigate the effect of ZnO-decorated GO nanocomposite material loaded with different weight percent of ZnO toward polysulfone (PSF) mixed-matrix membrane (MMM) performance enhancement. ZnO-decorated GO nanocomposite material was loaded with 1, 5, 10 and 20 wt. % ZnO was blended with PSF polymer and fabricated through phase inversion process. The performance of the fabricated MMMs were evaluated by measuring membrane permeability, bovine serum albumin rejection (BSA) and flux recovery ratio (FRR). Experiment results demonstrated that the PSF/ZnO-GO MMM performances were greatly improved where 10 wt. % ZnO loaded into ZnO-decorated GO nanomaterial exhibited the highest permeability (5.35 L/m2·h·bar) and BSA retention at all pH state among all fabricated mixed-matrix membranes. Additionally, FRR was also dramatically improved attributed to the smoother membrane surface. This work has shown that a well distribution of ZnO with the help of GO nanosheet as a dispersing agent blended with PSF polymer to form PSF/ZnO-GO MMM was a promising approach in creating better ultrafiltration (UF) membrane with a better hydrophilicity, permeability, and cleaning efficiency for the used in food industry in future.